2022
DOI: 10.1101/2022.10.16.512400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organelle proteomic profiling reveals lysosomal heterogeneity in association with longevity

Abstract: Lysosomes are active sites to integrate cellular metabolism and signal transduction. A collection of proteins enriched at lysosomes mediate these metabolic and signaling functions. Both lysosomal metabolism and lysosomal signaling have been linked with longevity regulation; however, how lysosomes adjust their protein composition to accommodate this regulation remains unclear. Using large-scale proteomic profiling, we systemically profiled lysosome-enriched proteomes in association with different longevity mech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Our work further extends these studies by uncovering many additional LEL subpopulations based on their membrane composition. Recent proteomic studies revealed the heterogeneity of lysosome proteome between different tissues (Yu et al, 2024). In the future, it would be interesting to explore if specific LEL subpopulations are also differentially enriched in distinct tissues and cell types and if these subpopulations are differentially susceptible in aging and disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work further extends these studies by uncovering many additional LEL subpopulations based on their membrane composition. Recent proteomic studies revealed the heterogeneity of lysosome proteome between different tissues (Yu et al, 2024). In the future, it would be interesting to explore if specific LEL subpopulations are also differentially enriched in distinct tissues and cell types and if these subpopulations are differentially susceptible in aging and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond LAMP and LIMP proteins, proteomic studies have identified over 100 different lysosomal membrane proteins, including ion channels, transporters, and exchangers (Akter et al, 2023; Bagshaw et al, 2005; Lubke et al, 2009; Muthukottiappan and Winter, 2021; Schroder et al, 2010; Yu et al, 2024). The lysosomal membrane also serves as a hub for various proteins that dynamically and transiently assemble on it including components of the nutrient sensing mTORC pathway such as mTORC1, Ragulator, and Raptor (Perera and Zoncu, 2016; Rogala et al, 2019; Sancak et al, 2010; Sancak et al, 2008; Settembre et al, 2013; Zoncu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The global proteome pro ling was processed as described previously with the following modi cations. 34,35 The frozen tissue was resuspended and lysed in 50mM Ammonium bicarbonate, 1 mM CaCl2 by 3 min of sonication, then 50 ug of tissue lysate were digested using 1 ug of trypsin for 12 hours at 37°C. Digested peptides concentration was measured using a colorimetric peptide assay kit (Thermo Fischer Scienti c, cat.…”
Section: Mass Spectrometry-based Proteome Pro Lingmentioning
confidence: 99%
“…While SPIONs can be applied to virtually any cell line with a functional endocytic pathway, they cannot be used for in vivo studies using animals, which were performed recently for TMEM-IPs in both Caenorhabditis elegans and mice. 21,22 Furthermore, both approaches could possibly affect the cells' proteome and therefore the results of the experiment. To date, the effect of overexpression of TMEM192, a lysosomal membrane protein of so-far unknown function, 23 has not been investigated, despite the increasing use of this approach in lipidomic, 24 metabolomic, 25 and proteomic 26 studies.…”
Section: ■ Introductionmentioning
confidence: 99%